Proceedings of the 22nd Annual International ACM SIGIR Conference on Research and Development in Information Retrieval 1999
DOI: 10.1145/312624.312677
|View full text |Cite
|
Sign up to set email alerts
|

Combining multiple evidence from different types of thesaurus for query expansion

Abstract: Automatic query expansion has been known to be the most important method in overcoming the word mismatch problem in information retrieval. Thesauri have long been used by many researchers as a tool for query expansion. However only one type of thesaurus has generally been used. In this paper we analyze the characteristics of dierent thesaurus types and propose a method to combine them for query expansion. Experiments using the TREC collection proved the eectiveness of our method over those using one type of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
1
3

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(69 citation statements)
references
References 21 publications
0
65
1
3
Order By: Relevance
“…Mandalas performed an in depth comparison between a variety of term expansion methods and combination approaches in [16] and found co-occurrence to be the most effective. There seems to be little doubt that generally speaking co-occurrence is the most effective way of increasing query relevance through term expansion.…”
Section: Term Expansionmentioning
confidence: 99%
“…Mandalas performed an in depth comparison between a variety of term expansion methods and combination approaches in [16] and found co-occurrence to be the most effective. There seems to be little doubt that generally speaking co-occurrence is the most effective way of increasing query relevance through term expansion.…”
Section: Term Expansionmentioning
confidence: 99%
“…Mandala et al [31] proposed a method to combine three different thesaurus types for query expansion. Bodner et al [27] combined WordNet and co-occurrence based thesauri for query expansion.…”
Section: Related Workmentioning
confidence: 99%
“…ఴ హనమఽ(vAhanamu)/vehicle etc. It's observed that the thesaurus-based QE techniques have not been as successful [8].…”
Section: A Thesaurusmentioning
confidence: 99%